2018
DOI: 10.1186/s12879-018-3464-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of IgA-protease genotypes in mucosal and invasive isolates of Haemophilus influenzae in Sweden

Abstract: BackgroundSeveral different IgA-proteases exist in Haemophilus influenzae. The variants have been suggested to play differential roles in pathogenesis, but there is limited information on their distribution in clinical isolates. The objective of this study was to investigate the distribution of IgA-protease genotypes in H. influenzae and assess the association between IgA-protease genotype and type of clinical infection.MethodsWe performed PCR-screening of the IgA-protease gene variants in two cohorts of clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Another limitation relates to the reported decrease in the Ig levels after gastrointestinal digestion, while their most effective targeted effect could be in the oral cavity, which could not be assessed in the present study. So, future studies should assess the persistence of the anti-SARS-CoV-2 IgA and IgG in the intestinal content, simulating also the action of the oral enzymatic and microbial metabolism; and explore the action of possible Ig-degrading proteases from the microorganisms that could be present in the infant gut microbiota [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation relates to the reported decrease in the Ig levels after gastrointestinal digestion, while their most effective targeted effect could be in the oral cavity, which could not be assessed in the present study. So, future studies should assess the persistence of the anti-SARS-CoV-2 IgA and IgG in the intestinal content, simulating also the action of the oral enzymatic and microbial metabolism; and explore the action of possible Ig-degrading proteases from the microorganisms that could be present in the infant gut microbiota [ 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study identified this gene in 46% of the strains from the respiratory tract, but in only 19% of the invasive strains. No correlation was found between the type of respiratory tract infection and the presence of the gene [48]. The protease appears to play a role in intracellular survival [49].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical isolates from the upper respiratory tract (URT) were obtained from nasopharyngeal samples analyzed at the clinical microbiology laboratory at Skåne University Hospital (Lund/Malmö, Sweden). Blood and cerebrospinal fluid isolates used in this study were from a collection of invasive clinical isolates obtained in Sweden between 1997 and 2009 and previously described by Resman et al ( 13 , 37 ). Tonsil specimens were obtained from patients undergoing tonsillectomy with the indications of hypertrophy or recurrent acute tonsillitis (ethics approval number BD46/2007) at Skåne University Hospital ( 38 ).…”
Section: Methodsmentioning
confidence: 99%